2017
DOI: 10.1097/id.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Versus Delayed Loading of Postextraction Implants

Abstract: IL does not negatively influence the long-term prognosis of implants inserted into fresh extraction sockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A detailed description of the primary stability is provided in Toljanic et al 10 Additionally shown that immediate loading had similar long-term results as the conventional delayed protocol. 31 These mentioned studies may indicate that the implant losses we saw in this follow-up are unlikely caused by the immediate loading, but rather due to poor maintenance leading to peri-implantitis.…”
Section: Inclusion Criteriamentioning
confidence: 78%
See 1 more Smart Citation
“…A detailed description of the primary stability is provided in Toljanic et al 10 Additionally shown that immediate loading had similar long-term results as the conventional delayed protocol. 31 These mentioned studies may indicate that the implant losses we saw in this follow-up are unlikely caused by the immediate loading, but rather due to poor maintenance leading to peri-implantitis.…”
Section: Inclusion Criteriamentioning
confidence: 78%
“…However, long-term studies with immediately loaded implants in the edentulous maxillae also report good implant survival, such as the follow-up presented by Cassetta with an implant survival rate of 97.9% after 10 years 29 and Testori et al that observed a survival rate of 95.1% after 10 years 30. In another study by Testori et al that compared immediate and delayed loading in fresh extraction sites, it was shown that immediate loading had similar long-term results as the conventional delayed protocol 31. These mentioned studies may indicate that the implant losses we saw in this follow-up are unlikely caused by the immediate loading, but rather due to poor maintenance leading to peri-implantitis.…”
mentioning
confidence: 90%
“…It must be emphasized that all the included studies concerning time for implant placement involved single tooth replacements and the patient perceptions in cases with multiple tooth extractions and provisional prosthesis may be different as reported by Testori and coworkers (Testori et al, 2004(Testori et al, , 2017.…”
Section: Implant Placementmentioning
confidence: 99%